MODULATION OF OXIDATIVE STRESS BY ABHRAK BHASMA IN DROSOPHILA MELANOGASTER - Subedi, Rambhadur P; Vartak, Rekha R; Kale, Purushottam G (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Management of aging is one of the most actively researched areas in biology. Ayurvedic preparations such as Abhrak Bhasma (AB) have been used for improving longevity and regenerative therapy as well as in treating various ailments. Modes of action of such Ayurvedic preparations are poorly understood at molecular level. Current investigation tests the efficacy of AB in modulating various parameters linked to oxidative stress. Methods: Drosophila melanogaster was used as a model system to test the efficacy of AB in inducing antioxidant machinery. Drosophila flies were fed on diet supplemented with AB at larval and adult stages. Subsequently, various parameters, catalytic as well as non-catalytic, related to antioxidant machinery were analyzed. Results: AB has been found to modulate the activity of superoxide dismutase and catalase enzymes as well as the total reduced glutathione (GSH) content. Larvae and adults feeding on diet supplemented with AB exhibit significantly lower levels of total GSH content (decrease of about 40â€“70% for larvae, while 31â€“36% for adults) and without any conclusive effect on GSH:oxidized glutathione ratio, free radical scavenging capacity, and extent of lipid peroxidation. These larvae and adults fed on diet supplemented with AB also exhibited an increase in the level of transcription of cap nâ€ collar C, heat shock protein 70, and catalase genes (â‰¥1.5 fold, except in few cases). Conclusion: Overall, AB alters various parameters linked to antioxidant machinery in D. melanogaster. The induced components may provide protection to the organism during stressful conditions.